Statistics for engineers and scientists - Navidi, William Cyrus (McGraw-Hill Education, 2015)
Statistics for Engineers and Scientists stands out for its crystal clear presentation of applied statistics. This edition features a unique approach highlighted by an engaging writing style that explains difficult concepts clearly, along with the use of contemporary real world data sets, to help motivate students and show direct connections to industry and research.